2020
DOI: 10.1158/1538-7445.am2020-5118
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5118: Proteogenomics characterization of HPV-negative head and neck squamous cell carcinomas

Abstract: Patients with head and neck squamous cell carcinomas (HNSCCs) are treated with surgery, radiation, chemotherapy, and limited targeted therapies. Compared to human papillomavirus (HPV)-positive HNSCCs, HPV-negative cases have worse treatment response and prognosis and represent an unmet clinical need. We performed comprehensive proteogenomic characterization of tumor specimens, matched normal adjacent tissues (NATs), and blood samples from 109 HPV-negative HNSCC patients. This cohort is dominated by tumors from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In Fig. 1 , panel E, the prognostic value of the immune signature was further validated in the HNSCC CPTAC cohort, as described by Huang et al [ 11 ]. The cohort consisted of 108 HPV-negative patients.…”
Section: Resultsmentioning
confidence: 89%
“…In Fig. 1 , panel E, the prognostic value of the immune signature was further validated in the HNSCC CPTAC cohort, as described by Huang et al [ 11 ]. The cohort consisted of 108 HPV-negative patients.…”
Section: Resultsmentioning
confidence: 89%
“…These authors suggested that EGFR ligands, rather than the receptor, are the major activator of EGFR pathway activity in this cancer type. Ligand abundance may be a more appropriate biomarker to select patients for anti‐EGFR monoclonal antibodies, which have shown only modest activity in unselected patient populations with head and neck cancer [76–78].…”
Section: Multi‐omic Analysismentioning
confidence: 99%
“…Initial single‐tumor cohort discovery studies in colorectal, breast and ovarian cancers used label‐free quantification and iTRAQ [27, 72, 73]. Subsequent studies have utilized TMT labeling and DIA for orthogonal validation [74–76].…”
Section: Multi‐omic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Using the mass spectrometry data sets from 10 tumor types characterized by CPTAC projects, we created a python package, named as 'cptac_glyco', to provide the unified access to identified glycopeptides of CPTAC cancer glycoproteomics data, containing 90,661 Nlinked glycopeptides from 2,194 proteins. The 10 cancer types include breast carcinoma (BRC) (Krug et al, 2020), clear cell renal cell carcinoma (ccRCC) (Clark et al, 2019), colorectal carcinoma (CRC) (Vasaikar et al, 2019), glioblastoma (GBM) (Wang, L. et al, 2021), head and neck squamous cell carcinoma (HNSCC) (Huang et al, 2021), lung squamous cell carcinoma (LSCC) (Satpathy et al, 2021), lung adenocarcinoma (LUAD) (Gillette et al, 2020), ovarian serous cystadenocarcinoma (OVC) (Hu et al, 2020), pancreatic ductal adenocarcinoma (PDAC) (Cao et al, 2021), and uterine corpus endometrial carcinoma (UCEC) (Dou et al, 2020). Based on the standardized expression matrices, we developed GPnotebook for the comprehensive glycoproteomic data analysis based on IGPs.…”
Section: Introductionmentioning
confidence: 99%